INCREASE STUDENT INTEREST AND MOTIVATION THROUGH THE USE OF INTERACTIVE LEARNING MEDIA - Wibowo, Ari Anton; Trisnawati, Trisnawati (JLCEdu (Journal of Learning and Character Education), 2023)
Academic interest and motivation important because motivated students tend to do activities that help them to learn and achieve high in academic settings for students to be motivated. The object of this research is the application of the Student Team Achievement Division (STAD) strategy with web-based interactive media youtube.com in increasing interest and motivation in learning Integrated Thematic. The type of research used is classroom action research or Classroom Action Research. This research was carried out in two cycles, cycle I had two meetings and cycle II had one meeting. Data collection techniques in this study used observation, interviews, documentation and field notes. With the results of the study, the hypothesis is accepted. This can be seen based on the achievement of each learning motivation indicators include: 1) Paying attention to teacher explanation in the precycle 8 students (60.2%), in cycle II increasing to 12 students (83.1%), 2) Showing readiness and interest in participating in learning in precycle 9 students (62.5%), in cycle II increasing to 12 students (78.4%), 3) Diligent in doing tasks in precycle 7 students (53.4%), in cycle II increased to 12 students (85%), 4) Asking and answering questions in precycle 4 students (30.7%), in cycle II increased to 11 students (76.4%), 5) students active during the learning process in precycle 5 students (35%), in cycle II increased to 11 students (78.9%). This percentage shows an increase in student motivation interest because it has reached the target of 75%.